From slave abuse to hate crime : the criminalization of racial violence in American history - Aaronson, Ely, 1973-; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
This book explores the complex ways in which political debates and legal reforms regarding the criminalization of racial violence have shaped the development of American racial history. Spanning previous campaigns for criminalizing slave abuse, lynching, and Klan violence and contemporary debates about the legal response to hate crimes, this book reveals both continuity and change in terms of the political forces underpinning the enactment of new laws regarding racial violence in different periods and of the social and institutional problems that hinder the effective enforcement of these laws. A thought-provoking analysis of how criminal law reflects and constructs social norms, this book offers a new historical and theoretical perspective for analyzing the limits of current attempts to use criminal legislation as a weapon against racism.
1. Towards a historical and sociological analysis of the criminalization of racial violence -- 2. Progressive criminalization at the heart of darkness?: The legal response to the victimization of slaves in the colonial and antebellum South -- 3. 'Social equality is not a subject to be legislated upon': the rise and fall of federal pro-black criminalization policy, 1865-1909 -- 4. 'We bring it out in the open, where it can be seen and dealt with': campaigning for criminalization reform in the long civil rights movement, 1909-1968 -- 5. Criminalizing racial hatred, legitimizing racial inequality: hate-crime laws and the new politics of pro-black criminalization -- 6. Conclusion: criminalization reform and egalitarian social change: an uneasy relationship.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: African Americans -- Crimes against -- History; Hate crimes -- United States -- History; Violence -- United States -- History; Violent crimes -- United States -- History; United States -- Race relations -- History; Electronic books